Sources of soft budget constraints in the structure of autonomous public healthcare centres - Babczuk, Arkadiusz; Kachniarz, Marian (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
Most of the public hospitals in Poland are heavily challenged to meet the costs of their operations. They are in severe debt and many of them face the risk of insolvency and loss of operability. Since a huge majority of Polish hospitals are operated by local authorities, we decided to focus just on this type of hospitals in this paper. However, our conclusions may as well be generalized to cover all the autonomous public healthcare centres. In this paper we discuss the sources of soft budget constraints, inherent to the legal form of autonomous public healthcare centres. We start with presenting the concept of soft budget constraints and point out the relationships between the concept and the insolvency of hospitals operated by local authorities and of the local authorities. The second part deals with the mechanisms of soft budget constraints development. The third part presents the nature and principles of financial governance of autonomous public healthcare centres. The fourth part is a listing of changes in the operating principles of healthcare service providers. The final discussion focuses on the consequences of financial instability of autonomous healthcare centres borne by their founding bodies
Argumenta Oeconomica, 2012, Nr 1 (28), s. 181-214
Keywords: soft budget constraints’; healthcare services; autonomous public healthcare centres; polityka budżetowa; opieka zdrowotna; rynek usług zdrowotnych; zakłady opieki zdrowotnej